Risk Factors for Stunting in School Children at Poboya Elementary School - A, Madinah; Rahman, Nurdin (Journal of Health and Nutrition Research, 2022)
Stunting is a condition of malnutrition that describes stunted growth, which has been going on for a long time and requires time to recover. Poboya gold mining is the largest source of the entry of mercury metal, the danger posed is that it affects growth. This study aims to determine the risk factors for stunting in school children at SDN Poboya Palu. This type of research is quantitative with the case control method. The number of samples used in this study were 171 respondents consisting of 57 cases and 114 controls with a ratio of 1: 2. Sampling using total sampling technique. Data on macro nutrition, education, employment, family income and food security were obtained through interviews using a questionnaire. Data analysis used univariate and bivariate analysis. Data obtained from statistical analysis using the Odds ratio (OR) test. The results showed macro nutrition (carbohydrate OR = 260 (95% CI 112-600), protein OR = 2.462 (95% CI 1.284-4.719), fat OR = 2.244 (95% CI 1.1694.309)), maternal education OR 2.708 (95% CI 1.377-5.326), maternal occupation OR = 3.478 (95% CI 1.790-6.757), family income OR = 3.076 (95% CI 1.592-5.944) and food security OR = 4.706 (95% CI 2.365-9.365). In research which is a risk factor for the incidence of stunting macro nutritional intake (protein and fat), mother's education, maternal work, family income and household food security.